Influence of past climate change on phylogeography and demographic history of narwhals, Monodon monoceros. Issue 1925 (29th April 2020) - Louis, Marie; Skovrind, Mikkel; Samaniego Castruita, Jose Alfredo; Garilao, Cristina; Kaschner, Kristin; Gopalakrishnan, Shyam; Haile, James S.; Lydersen, Christian; Kovacs, Kit M.; Garde, Eva; Heide-Jørgensen, Mads Peter; Postma, Lianne; et al.
Abstract : The Arctic is warming at an unprecedented rate, with unknown consequences for endemic fauna. However, Earth has experienced severe climatic oscillations in the past, and understanding how species responded to them might provide insight into their resilience to near-future climatic predictions. Little is known about the responses of Arctic marine mammals to past climatic shifts, but narwhals ( Monodon monoceros ) are considered one of the endemic Arctic species most vulnerable to environmental change. Here, we analyse 121 complete mitochondrial genomes from narwhals sampled across their range and use them in combination with species distribution models to elucidate the influence of past and ongoing climatic shifts on their population structure and demographic history. We find low levels of genetic diversity and limited geographic structuring of genetic clades. We show that narwhals experienced a long-term low effective population size, which increased after the Last Glacial Maximum, when the amount of suitable habitat expanded. Similar post-glacial habitat release has been a key driver of population size expansion of other polar marine predators. Our analyses indicate that habitat availability has been critical to the success of narwhals, raising concerns for their fate in an increasingly warming Arctic.